2024
DOI: 10.1038/s41467-024-47194-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced polarization switching characteristics of HfO2 ultrathin films via acceptor-donor co-doping

Chao Zhou,
Liyang Ma,
Yanpeng Feng
et al.

Abstract: In the realm of ferroelectric memories, HfO2-based ferroelectrics stand out because of their exceptional CMOS compatibility and scalability. Nevertheless, their switchable polarization and switching speed are not on par with those of perovskite ferroelectrics. It is widely acknowledged that defects play a crucial role in stabilizing the metastable polar phase of HfO2. Simultaneously, defects also pin the domain walls and impede the switching process, ultimately rendering the sluggish switching of HfO2. Herein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Shi et al demonstrated that ferroelectricity of Hf 0.5 Zr 0.5 O 2 epitaxial thin films was related to different terminations of La 0.7 Sr 0.3 MnO 3 (LSMO) layer [29]. Zhou et al reported enhanced ferroelectricity in the HfO 2 ultrathin films using La 3+ -Ta 5+ co-doped strategy [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al demonstrated that ferroelectricity of Hf 0.5 Zr 0.5 O 2 epitaxial thin films was related to different terminations of La 0.7 Sr 0.3 MnO 3 (LSMO) layer [29]. Zhou et al reported enhanced ferroelectricity in the HfO 2 ultrathin films using La 3+ -Ta 5+ co-doped strategy [30].…”
Section: Introductionmentioning
confidence: 99%
“…It was also proposed the epitaxial orientation significantly affects strain-induced phase transitions in ferroelectric BaTiO 3 films [32]. However, most studies on the ferroelectric properties of HfO 2 -based epitaxial films have focused predominantly on (111)-orientation [9,17,18,20,[28][29][30][37][38][39], leaving the correlation between crystalline orientation and ferroelectricity unexplored. Few studies have addressed on (001)-oriented HfO 2 -based epitaxial films [40,41], despite this orientation being more aligned with the direction of spontaneous polarization in ferroelectric hafnia-based films, which is crucial for understanding ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%